Posebnosti uresničevanja pravice do stavke v javnem sektorju - Končar, Polonca (Delavci in delodajalci, 2024)
The number of strikes in public sector has recently been increasing. The shortcomings of the current regulations and practice is becoming more and more obvious. They are related to the outdated Strike Act. On the other side, the sectoral legislation and autonomous legal sources are not in compliance with the Strike act, the Constitution of the RS, the binding international norms and their interpretations. The contribution in the first place draws the attention to the relation between international and national law. Next, the authoress points out basic principles and interpretations of the ILO Convetion No. 87 and the European Social Charter (revised) which relate to the strike in public sector. The last part of the contribution is dedicated to the dilemas regarding the concrete exercise of the two collective actions in 2024, namely the strike/ protest of judges and the strike of doctors and dentists.
Keywords: binding nature of interpretations of international norms; definition of the strike; European Social Charter (revised); freezing of the strike; illegality of the strike; ILO Convention No. 87; javni sektor; javni uslužbenci; minimal services; nezakonitost stavke; organizatorji stavke; pravica do stavke; public sector; restrictions of the right to strike; Slovenija; stavke; Strike Act; strike organizers; Zakon o stavki